Pengaruh Poster Terhadap Perubahan Perilaku Penjamah Makanan Di Kantin Politeknik Negeri Jember - Muhammad Iqbal; Nina Agusti Winarsih (Jurnal Gizi, 2020)
Hygiene sanitation of food in the canteen is important because of the existence of a canteen to ensure the health of canteen users. The behavior of food handlers determines the quality of food served. During this time there were still many cases of food handlers who lacked good behavior as food handlers. This study aims to improve the behavior of food handlers in the Jember State Polytechnic canteen using poster media without counseling. This research is a quasi-experimental study with the design of one group pretest posttest. Respondents from this study came from 10 food stands at the Jember State Polytechnic canteen. The first month was given a pretest and poster installation. Then the poster was left for 2 months and posttest. Data retrieval uses a behavior checklist form that has been validated. The results of statistical analysis show that the value of p = 0.9981 which means > 0.05 (alpha). That is, there were no significant changes between before and after the poster was given. This means that giving posters without counseling was not effective in changing the behavior of food handlers for the better. Viewed from the poster media itself there are no problems. However, explanations such as short presentations or counseling are needed so that food handlers change their behavior.Keywords: Canteen, Counseling, Food Handler Behavior, Posters